P18.01.A The applicability of established clinical and histopathological risk factors for tumor recurrence during long-term perioperative care in meningioma patients. (5th September 2022) - Lüthge, S; Steinbicker, A; Schipmann, S; Streckert, E M S; Hess, K; Grauer, O; Paulus, W; Stummer, W; Brokinkel, B; Spille, D C
Abstract: Background: Risk factors for the prediction of late-onset tumor recurrence in meningioma patients are sparse but needed to estimate duration and control intervals during long-term follow-up in meningioma patients. In this study, we therefore analyzed the value of established risk factors for postoperative meningioma recurrence for the prediction of long-term prognosis in a large, single-center series. Material and methods: Correlations of established clinical (age, sex, tumor location, extent of resection), radiological (postoperative tumor volume) and histopathological variables (WHO grade, brain invasion) with tumor relapse were analyzed separately after 3, 5, and 10 years following microsurgery for primary diagnosed intracranial meningioma between 1991 and 2021 in uni- and multivariate analyses. The prognostic value was compared to findings in the entire cohort. Results: Within a median follow-up of 29 months (range: 0-307 months), recurrence was observed in 141 patients (12%) after a median PFS of 36 months. PFS among the entire cohort (n=1218) at 3, 5, 10 and 15 years postoperatively were 90%, 84%, 74% and 70%, respectively. Among all patients included, skull base location (HR: 1.51, 95%CI 1.05-2.16; p=.026), Simpson ≥IV resections (HR: 2.41, 95%CI 1.52-3.84; p<.001), high-grade histology (HR: 3.70, 95%CI 2.50-5.47; p<.001) and male gender (HR: 1.46, 95%CI 1.01-2.11; p=.042) were independent risk factors for recurrence. Skull base location (HR: 1.92, 95%CI 1.17-3.17; p=.010 and HR: 2.02, 95%CI 1.04-3.95; p=.038) and high-grade histology (HR: 1.87, 95%CI 1.04-3.38; p=.038 and HR: 2.29, 95%CI 1.07-4.01; p=.034) but not subtotal resection (HR: 1.53, 95%CI .68-3.45; p=.303 and HR: 1.75, 95%CI .52-5.96; p=.369) remained independently correlated with recurrence after an event-free PFS of at least three (n=485) and five years (n=346), respectively. Similarly, postoperative tumor volume was related with recurrence in the entire cohort (p<.001) but not beyond a follow-up of ≥ three years (p>.05). In 147 patients with a follow-up of ≥ ten years, ten recurrences occurred, and no correlation was found with any of the analyzed variables. Conclusion: Skull base tumor location and high-grade histology but not the extent of resection should be considered when planning follow-up duration and intervals following ≥5 years after meningioma surgery. Tumor relapses following more than ten years after surgery are very rare, and corresponding predictors are lacking.